Understanding energy efficiency using a socioeconomic framework: the case of paddy farming in Malaysia - Siti ‘Aisyah Baharudin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The agriculture sector is one of the contributors to energy use either as production input or bioenergy output. The utilization of energy use is based on the Cobb-Douglas production theory. Nevertheless, several factors affecting energy use in paddy production include fuel for running machinery, electricity for irrigation, fertiliser for improving soil fertility, pesticides for pest control, and planting seeds. Albeit the relationship between energy use and agricultural productivity is well examined in the literature, the results are mixed. Some studies argue that higher energy use tends to higher agricultural productivity, while others found that energy use efficiency leads to higher productivity. This study investigates farmers’ socioeconomic status in paddy production based on the statistical analysis of paddy productivity, farmers’ income, and production cost in Malaysia’s MADA granary areas. Besides, it utilizes the Energy Analysis approach to analyze energy efficiency based on inputs use selected by farmers. The results show that the harvested area does not affect the farmers’ income, while productivity positively affects farmers’ income. Production costs are not influenced by socioeconomic variables such as ownership and harvested area as they depend on farmers’ willingness to pay for inputs. The energy efficiency in MADA is 6.35, which indicates that farmers can obtain at least six times larger paddy productivity compared to the inputs used in production activities.